The Role of University Faculties in Sustainable Development in Higher Education in Tamilnadu, India - Mrs. E. Manju, Ms. U. Geetha, Dr. P. S. Venkateswaran, Dr. Shalini Sundar, Dr. K.Chandrasekar (International Journal of Advanced Science and Technology, 2020)
In India, about sustainability in higher education related research studies are very less and the students are having less knowledge about it. This paper tries to identify the role of University faculties in higher education for the sustainable development in Tamilnadu, India. This research study was carried out in the selected twelve arts, science and engineering University faculties. This study covers both male and female faculty members and their awareness and ideologies about the development of sustainability in higher education. Descriptive research design and convenient sampling method was adopted and 976 faculty responses were obtained. The result shows that the roles of University faculties are engaging the students through making them aware and understand about sustainability in higher education. If University faculties can educate the students for better utilization of resources, it helps to protect the higher education effectively. Sustainability in higher education practices creates attractive employment opportunity to the students. Keyword:. University, Faculty, Knowledge sharing, Sustainability in higher education, culture, Higher education, Tamilnadu